Analysis of Issues in Islamic Financial Literacy and Solutions to Increase Investment Interest Among the Younger Generation - Nurul Khasanah; Mila Amelia; Dini Selasi (Jurnal Pengabdian Nusantara, 2026)
For This research analyzes the problem of low Sharia financial literacy among the youth and identifies solutions that can be applied to increase their investment interest in the Sharia capital market. Although Sharia investment is increasingly popular, youth participation is still constrained. OJK data (2022) shows that the national Sharia financial literacy rate is only around 9.14%, which is far below conventional literacy (49.68%), reflecting a gap in understanding among the productive age group. This study utilizes a literature study method by analyzing various secondary sources such as scientific journals and official documents. The main findings indicate that Sharia financial literacy has a positive and significant influence on the investment interest of the youth. A sound understanding of Sharia principles, such as the prohibition of riba (interest), gharar (excessive uncertainty), and maysir (speculation), as well as Sharia-compliant products (Sharia stocks, sukuk), shapes conviction, attitude, and investment decisions that align with religious values. To overcome the challenge of low literacy, a comprehensive and integrated strategy is required : (1) Systematic Education and Socialization of Sharia literacy through educational institutions and the utilization of digital media and gamification; (2) Development of Sharia Investment Products that are innovative, affordable, and user-friendly; (3) Mentoring and Coaching through investment communities ; and (4) Active Stakeholder Collaboration (government, financial institutions, academics). This research is expected to provide a practical contribution to the development of Sharia financial literacy and support the growth of the Sharia capital market in Indonesia.